IMPLEMENTASI PROGRAM KAMIS TANGKAS NUMERASI SEBAGAI UPAYA PENINGKATKAN NUMERASI DI SEKOLAH DASAR - Niza Nurul Husna; Sakinatul Qulub; Desi warsita; Hatyka sari; Dinda putri; Syafruddin Muhdar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of the KATAMU Program (Thursday Numeracy Challenge) as an effort to improve elementary school students’ numeracy skills. This study used a descriptive qualitative approach with data collection techniques through observation and documentation. The KATAMU Program was conducted routinely every Thursday through interactive numeracy activities involving students from grades I to VI. The results showed that the program had a positive impact on students’ numeracy skills, especially in terms of accuracy, carefulness, and speed in solving problems. In addition, the program also increased students’ activeness, confidence, and enthusiasm in learning activities. However, several challenges were still found, such as differences in students’ abilities and difficulties in understanding verbal instructions. Therefore, the KATAMU Program can be used as an innovative learning activity to support numeracy development in elementary schools.